22 CARDIAC AMYLOIDOSIS: SYMPTOMATIC IMPROVEMENT WITH HYDRALAZINE AND ISORDIL. Issue 1 (1st January 2007) - Hess, M. L.; Prabhakar, S.
Abstract : Case: S.M. is a 55-year-old lady who presented to an outlying hospital with a 2- to 3-week history of shortness of breath and lower extremity edema. There was no significant past medical history. Pertinent findings included echocardiogram with a normal EF, biatrial enlargement, pulmonary hypertension, and left ventricular hypertrophy with ground-glass appearance. Chest radiography showed bilateral pleural effusions, right greater than left, and she was anemic. During hospitalization, nonsustained ventricular tachycardia was identified and an AICD was placed. She underwent bone marrow biopsy, which was 80% cellular with plasma cells and amyloid deposition, and was transferred to the university hospital. SPEP and UPEP showed monoclonal spike. Repeat echocardiography showed a ground-glass appearance with an EF of 50%, marked biatrial enlargement, a small pericardial effusion, normal valves, and moderate tricuspid regurgitation. A diagnosis of cardiac amyloidosis secondary to multiple myeloma was made, and the patient underwent right heart catheterization, which showed RA equal to 16 mm Hg, RV of 58/16, PA of 60/21, PCW equal to 18, and cardiac output of 4.6 L/min. The patient was then started on a 72-hour infusion of β-natriuretic peptide at 0.01 μg/kg/min to increase venous capacity and decrease pulmonary vascular resistance. A transition from Natrecor was made to a program of hydralazine (25 mg tid) and Isordil (10 mg tid). The patient was discharged and medications were up-titrated on an outpatient basis. She continued to improve to a functional class II level and was being considered for bone marrow transplantation. Repeat right heart catheterization was performed, which showed improvement with the RA pressure equal to 9, RV of 45/9, PA of 48/28, and a wedge of 17. She was continued on a program of aldactone 25 mg daily, bumetadine 2 mg daily, hydralazine 37.5 mg tid, Isordil 20 mg tid, mexilitine 150 mg tid, and Coumadin for intermittent atrial fibrillation. The patient was well at home, carrying on a full and active lifestyle when she experienced an episode of sudden death that was unresponsive to AICD therapy. Postmortem interrogation of AICD showed ventricular tachycardia and ventricular fibrillation. This case demonstrates a significant improvement in functional capability of the restrictive cardiomyopathy of amyloidosis by increasing venous capacity and decreasing pulmonary vascular resistance and systemic vascular resistance with hydralazine and Isordil with an increase in functional capacity.